2019
DOI: 10.1002/ptr.6378
|View full text |Cite
|
Sign up to set email alerts
|

Lathyrus sativus diamine oxidase counteracts histamine‐induced cell proliferation, migration and pro‐angiogenic mediators release in human colon adenocarcinoma cell line Caco‐2

Abstract: Because histamine is a modulator of cancer cell proliferation and invasiveness, this study aimed at investigating the effect of Lathyrus sativus–derived diamine oxidase (LSAO) and its mechanism of action on Caco‐2 cell line, considering that LSAO catalizes the oxidative deamination of histamine to the corresponding aldehyde, NH3 and H2O2. Histamine (0.01–1 μM) caused a proliferative effect on Caco‐2 cells promoting cell migration, invasion and nitric oxide and vascular endothelial growth factor release. Histam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
(52 reference statements)
2
11
0
Order By: Relevance
“…Moreover, MMP-2 plays an role in the migration and invasion of tumor cells (Ni et al, 2019). Different studies have shown that MMP-2 contributes to the migration and metastasis of colon cancer cells (Ko et al, 2019;Pietrangeli et al, 2019). Studies have shown that increased expression of P2 × 7 receptor can increase the expression of MMP-2 and MMP-9 through NF-kB, ERK1/2 and Akt signals, and promote the migration of prostate cancer and breast cancer cells (Tafani et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MMP-2 plays an role in the migration and invasion of tumor cells (Ni et al, 2019). Different studies have shown that MMP-2 contributes to the migration and metastasis of colon cancer cells (Ko et al, 2019;Pietrangeli et al, 2019). Studies have shown that increased expression of P2 × 7 receptor can increase the expression of MMP-2 and MMP-9 through NF-kB, ERK1/2 and Akt signals, and promote the migration of prostate cancer and breast cancer cells (Tafani et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…LSAO was purified from L. sativus seedlings as previously described (Pietrangeli et al, 2019). The enzyme was characterized for protein content and enzymatic activity as reported (Pietrangeli, Federico, Mondovì, & Morpurgo, 2007), then aliquoted and stored at −20°C.…”
Section: Methodsmentioning
confidence: 99%
“…Control group cells were treated with pyrogen‐free sterile vehicle. TcdA and LSAO concentrations were selected according to our previous research studies (Esposito et al, 2016; Pietrangeli et al, 2019). For each experiment, LSAO treatment for 24 hr preceded TcdA challenge.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations